A Comprehensive Study of Pollution in Underground Water in Ballia City (International Journal of Food and Nutritional Sciences, 2022)
The Water pollution term is present or in future. referred to the addition of an excess of material to water that is harmful to humans , animals , or desirable aquatic lives. Or otherwise causes significant departures from the normal activities or various living communities in or near bodies of water1 . The national water commission stated that water gets polluted if it has been not of sufficiently high quality to be suitable for the highest uses people wish to make of it as in present or in future. The effect of sewage, industrial waste and agricultural drainage on plant and animal life in closed bodies of water is some time catastrophic. The accumulation of excessive plant nutrients called entrophication has occurred in lake erie, lake Washington at seattle, the lakes in the modison, Wisconsin area, and lake Zurich in Switzerland2. A particular certain number of individuals will get diseases and thus capable of contaminating the water with various infections agents. In addition , hospitals dispose of water products disposed from hospitals into water ways and ground water systems also cause pollution. Unfortunately the identification of specific infections agents in a water supply needs the analysis of vast numbers of samples by time consuming and sophisticated methods generally therefore routine monitoring of water supplies employs the MPN (most probable number) method. This enrichment leads to other slow process collectively referred to as natural aging of lakes4 . The Chemical Treatment methods have been used in many active mines . The mine discharge has been sent to a near by treatment plant where hydrated lime has been added . This has been following by an aeration of the water. The water has been placed in a large lagoons where the sludge created by the process saltless to the bottoms and a clear overflow gets discharged in to the bottom and a clear overflow gets discharged into the natural waters large influxes of strong and have been able to over them this buffering ability of water and bring about drastic drops in pH values. The effect of chemical pollutants on health is not well understood. Even information on the identity and amount of the chemicals . That are present in incomplete , although the use of chemical products every where is on the increase. Some natural waters are known to have injurious chronic effect from prolonged use . Therefore chemical contaminants that may enter the water supply from sources such as sewage effluents, the recycling of treated wastes , or percolation of wastes in to the underground water supply should be under suspicion until proved to be harmless by experiments with laboratory animals. Several waterborne infections diseases are directly related to polluted water. In addition the aquatic food chain acts to concentrate several toxic substances and it ascends from micro organisms through various predators and prey to fish eaten by seals, by certain birds or by people Organochlorineand organomercury pesticides , PBCs and some radioactive pollutants are confentrated this way. Well Water contaminated by nitrates from fertilizers run of posses a hazard to health particularly for infants.